The challenges of interventions to promote healthier food in independent takeaways in England: qualitative study of intervention deliverers' views - Louis Goffe; Linda Penn; Jean Adams; Vera Araujo-Soares; Carolyn D. Summerbell; Charles Abraham; Martin White; Ashley Adamson; Amelia A. Lake (BMC, 2018)
Abstract Background Much of the food available from takeaways, pubs and restaurants particularly that sold by independent outlets, is unhealthy and its consumption is increasing. These food outlets are therefore important potential targets for interventions to improve diet and thus prevent diet related chronic diseases. Local authorities in England have been charged with delivering interventions to increase the provision of healthy food choices in independent outlets, but prior research shows that few such interventions have been rigorously developed or evaluated. We aimed to learn from the experiences of professionals delivering interventions in independent food outlets in England to identify the operational challenges and their suggestions for best practice. Methods We used one-to-one semi-structured qualitative interviews to explore the views and experiences of professionals who were either employees of, or contracted by, a local authority to deliver interventions to increase the provision of healthier food choices in independent food outlets. Purposive sampling was used to recruit a sample which included men and women, from a range of professional roles, across different areas of England. Interviews were informed by a topic guide, and proceeded until no new themes emerged. Interviews were recorded, transcribed verbatim and analysed using the Framework method. Results We conducted 11 individual interviews. Participants focussed on independent takeaways and their unhealthy food offerings, and highlighted the advantages and disadvantages of intervention delivery methods, their evaluation and impact. The main barriers to implementation of interventions in independent takeaways were identified as limited funding and the difficulties of engaging the food outlet owner/manager. Engagement was thought to be facilitated by delivering intensive, interactive and tailored interventions, clear and specific information, and incentives, whilst accounting for practical, primarily financial, constraints of food businesses. Alternative intervention approaches, targeting suppliers or customers, were suggested. Conclusions Participants emphasised independent takeaways as particularly challenging, but worthwhile intervention targets. Participants perceived that interventions need to take account of the potentially challenging operating environment, particularly the primacy of the profit motive. Upstream interventions, engaging suppliers, as well as those that drive consumer demand, may be worth exploring. Rigorous, evidence-informed development and evaluation of such interventions is needed.